Correlation in estimating the degree of liver fibrosis using elastography and biochemical predictors of fibrosis, APRI and FIB-4 in a Mexican population from the National Medical Center of the West with chronic Hepatitis C Virus (HCV) infection. - Gerardo González-Macedo; Christian Jaramillo-Buendía; Jose Francisco Aguayo-Villaseñor; Manuel Osiris Hernández-Ceballos; Álvaro Ismael Calleros-Camarena (Annals of Hepatology)
Introduction and Objectives: Liver fibrosis is common in HCV infection, leading to clinically significant portal hypertension and decompensated cirrhosis with high morbidity and mortality. Transient elastography is a validated study for the measurement of liver fibrosis with good predictive value, but it is not available in most public institutions. There are non-invasive measurement methods for fibrosis available, such as the FIB-4 and APRI indices. To analyze the correlation between the degree of liver fibrosis measured by elastography with the APRI and FIB-4 indices in a Mexican population with chronic HCV infection. Materials and Patients: Cross-sectional, analytical, retrospective diagnostic test study. Information was obtained from the clinical records of HCV patients treated during the period from January 2017 to January 2019 in the Gastroenterology service of UMAE CMNO. Results: A total of 467 patients were retrospectively analyzed; 281 met the inclusion criteria, 66.2% female and 32.8% male. Median age was 60 years, with an interquartile range of 16 years. Median weight was 62.5 kg, BMI of 24.8. The predominant HCV genotype was 1a, corresponding to 64.5%, genotype 1b was 24.7%. Genotypes 2, 3, and 4 represented 5.4%, 4.6%, and 0.8% of the population respectively. 2.2% had HIV co-infection and 0.7% had hepatitis B co-infection. 58% had a fibrosis grade of F4, 17.1%: F1, 12.1%: F2, 11%: F3, and 1.8% without evidence of fibrosis (F0) according to the elastography results. There were no statistically significant differences between male and female participants (p=0.131). Sex did not impact the development of liver fibrosis. Spearman's correlation between APRI and FIB-4 indices with liver elastography was evaluated (Figure 1). A Rho value of 0.56 and a p-value < 0.001 was obtained for the APRI index and elastography. Similarly, the FIB-4 index also obtained a Rho value of 0.56 and a p-value < 0.001 with respect to elastography. For the APRI index, the calculated cutoff point for each ROC curve was the same (0.75), regardless of the degree of fibrosis. It was considered a good predictor of fibrosis. For the FIB-4 index, the calculated cutoff points matched in the subgroups of F0–F2 with an optimal cutoff value of 2.645, and in the subgroups of F3-F4 with an optimal cutoff point of 2.665. This suggests that this index is a good marker for distinguishing between grade F1 and advanced fibrosis grades (F3-F4) (Table 1). Conclusions: The APRI and FIB-4 indices are reliable and accurate predictors for estimating the degree of liver fibrosis in patients with chronic HCV infection, with a statistically significant correlation of the degree of liver fibrosis between the predictive indices and liver elastography.